2005
DOI: 10.1007/s10765-005-8106-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Polymethyl Methacrylate (PMMA) and Borosilicate Crown Glass BK7

Abstract: The thermal conductivity of polymethyl methacrylate (PMMA) and borosilicate crown glass BK7 has been studied. The transient hot-wire technique has been employed, and measurements cover a temperature range from room temperature up to 350 K for PMMA and up to 500 K for BK7. The technique is applied here in a novel way that minimizes all remaining thermalcontact resistances. This allows the apparatus to operate in an absolute way and with very low uncertainty. The method makes use of a soft silicone paste materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
64
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 11 publications
16
64
0
Order By: Relevance
“…Also, measurements presented only in graphical form have not been included. In all three cases, our previous measurements [4,5] performed with an uncertainty of 1.5 % agree very well with the present measurements performed with [12] the lower uncertainty of 1 %. Only at one temperature in BK7, the measurements are just over the mutual uncertainties of the two instruments.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Also, measurements presented only in graphical form have not been included. In all three cases, our previous measurements [4,5] performed with an uncertainty of 1.5 % agree very well with the present measurements performed with [12] the lower uncertainty of 1 %. Only at one temperature in BK7, the measurements are just over the mutual uncertainties of the two instruments.…”
Section: Resultssupporting
confidence: 90%
“…where the coefficients a i and the values of λ (298.15 K) are shown in [5], and Pyrex 774 [4], as well as measurements of other investigators, are also shown. We have chosen not to present here the values of investigators who report only one measurement and that at "room temperature" quoting no exact reference temperature, and no uncertainty in their measurements.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…This value has ranged from 0.02 to 0.1 mm 2 /s as obtained from different methods for other organic materials. [21][22][23] In these reports, it has been observed by Lim et al, 21 Assael et al, 22 and Cahill 23 that the variation observed in these measurements are the limitation of measurement techniques. Therefore, the variation in diffusivity value obtained in all four devices, in our case, may be due to the limitation of the measurement technique.…”
mentioning
confidence: 99%